CHINA’S GEOPOLITICAL DESIGN FOR EAST ASIA: TAIWANESE PIECE OF THE PUZZLE - Stekić, Nenad (The Policy of National Security, 2023)
China’s foreign and security policy preferences for East Asia are a multifaceted issue, with Taiwan playing a crucial role in this strategic puzzle. Beijing’s claim over Taiwan as its integral part is a key component of its geopolitical strategy in East Asia and an important constituent of regional security dynamics. This paper aims to delve into China’s patterns of such geopolitical design for East Asia, paying particular attention on Taiwan’s place within the newly introduced Indo-Pacific and attempts at multilateral alignments in the region. Author offers arguments for China’s East Asian ’’regionally tailored’’ policy and discusses potential strategic options ahead of Chinese leadership regarding US-led attempts to contain China geopolitically and militarily. In addition, the paper explores some Beijing’s concrete military and foreign policy responses, including its military policy over the East China Sea Air Defence Identification Zone and consequences derived from recently adopted strategy titled Taiwan Issue and China’s Unification in the New Era. Given Taiwan’s pivotal geopolitical position in China’s security policy, the paper assumes that it will be one of the principal sites where the contest for the emerging world order will be waged between China and the United States. China’s rise in the international system and the current politico-security tensions in the East Asian region as examples to argue that certain theoretical approaches, like the liberal Hegemonic Stability Theory, may no longer hold true, because international system is moving towards institutional separation into parallel entities, which could be a significant shift from the system that emerged after the Second World War.